Manufacturing a chimpanzee adenovirus‐vectored SARS‐CoV‐2 vaccine to meet global needs. Issue 1 (15th November 2021) - Joe, Carina C. D.; Jiang, Jinlin; Linke, Thomas; Li, Yuanyuan; Fedosyuk, Sofiya; Gupta, Gaurav; Berg, Adam; Segireddy, Rameswara R.; Mainwaring, David; Joshi, Amar; Cashen, Paul; Rees, Byron; et al.
Abstract: Manufacturing has been the key factor limiting rollout of vaccination during the COVID‐19 pandemic, requiring rapid development and large‐scale implementation of novel manufacturing technologies. ChAdOx1 nCoV‐19 (AZD1222, Vaxzevria) is an efficacious vaccine against SARS‐CoV‐2, based upon an adenovirus vector. We describe the development of a process for the production of this vaccine and others based upon the same platform, including novel features to facilitate very large‐scale production. We discuss the process economics and the "distributed manufacturing" approach we have taken to provide the vaccine at globally‐relevant scale and with international security of supply. Together, these approaches have enabled the largest viral vector manufacturing campaign to date, providing a substantial proportion of global COVID‐19 vaccine supply at low cost. Abstract : Well over a billion doses of the ChAdOx1 nCoV‐19 vaccine developed by The University of Oxford and AstraZeneca have been produced and distributed at low cost. This represents a substantial proportion of global COVID‐19 vaccine supply to date, especially in low‐ and middle‐income countries. The authors report on the development of the manufacturing process for the vaccine, and the process economics and distributed manufacturing approach involving bulk vaccine (drug substance) production on five continents.